Extracardiac anomalies in prenatally diagnosed heterotaxy syndrome. (4th March 2016) - Gottschalk, I.; Stressig, R.; Ritgen, J.; Herberg, U.; Breuer, J.; Vorndamme, A.; Strizek, B.; Willruth, A.; Geipel, A.; Gembruch, U.; Berg, C.
ABSTRACT: Objective: To assess the incidence and impact of extracardiac anomalies on the prognosis of fetuses with heterotaxy syndrome. Methods: All fetuses diagnosed with heterotaxy syndrome by three experienced examiners over a period of 14 years (1999–2013) were reviewed retrospectively. Results: In total, 165 fetuses with heterotaxy syndrome were diagnosed in the study period. One hundred and fifty (90.9%) had cardiac defects; extracardiac anomalies that did not involve the spleen were present in 26/165 (15.8%) cases. Of the total study cohort, termination of pregnancy was performed in 49 (29.7%) cases, intrauterine death occurred in 11 (6.7%), postnatal death occurred in 38 (23.0%) and 67 (40.6%) were alive at the latest follow‐up, resulting in a total perinatal and pediatric mortality of 59.4%. Among the 105 liveborn neonates, 15 (14.3%) had extracardiac anomalies with significant impact on the postnatal course: one neonate died following repair of an encephalocele, six had successful treatment for various types of intestinal malrotation and/or atresia and one underwent hiatal hernia repair; the remaining seven had biliary atresia, of which five died and the two survivors are awaiting liver transplantation. The status of the spleen was assessed in 93/105 liveborn children and was found to be abnormal in 84/93 (90.3%). There were three cases of lethal sepsis, all associated with asplenia. Of the 38 postnatal deaths, 29 (76.3%) had a cardiac cause, seven (18.4%) had an extracardiac cause and in two (5.2%) the reason was uncertain. Conclusions: Although the leading causes of death in fetuses and children with heterotaxy syndrome are cardiac, a small subset of fetuses have extracardiac anomalies with significant impact on outcome. These anomalies often escape prenatal detection, and therefore neonates at risk should be monitored for bowel obstruction, biliary atresia and immune dysfunction in order to allow timely intervention through a multidisciplinary approach. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.